How Employers Steal from Employees: The Untold Story - Bittle, Steven (Social justice, 2018)
This article critically examines wage theft by employers from employees. In addition to documenting how wage theft disproportionately affects marginalized workers, the article reveals how seldom these offenses are recognized as crimes and documents the normalization of wage theft through the neoliberal rhetoric that renders it unseen. Overall, we argue that wage theft extends far beyond the intentional, overt nonpayment of wages by atypical employers and encompasses many more insidious forms of stealing workers’ time and wages. The article concludes with suggestions for approaching wage theft as an opportunity to actively resist neoliberal morality in all its (dis)guises.